Mary Shelley die Frau, die Frankenstein erschuf - Warner, Amelia 1982- (2021)
The real-life story of Mary Shelley, and the creation of her immortal monster, is nearly as fantastical as her fiction. Raised by a renowned philosopher father in eighteenth-century London, Mary Wollstonecraft Godwin is a teenage dreamer determined to make her mark on the world, when she meets the dashing and brilliant poet Percy Shelley. So begins a torrid, bohemian love affair marked by both passion and personal tragedy that will transform Mary and fuel the writing of her Gothic masterwork
Orignal: Großbritannien, Luxemburg, USA, Irland 2018
Bildformat 2.40:1 (anamorph)
Extras: Behind the scenes ; Interviews Cast & Crew ; Deutscher und Original-Kinotrailer
Arthaus: 507400
Keywords: Shelley, Mary -- 1797-1851; Shelley, Percy Bysshe -- 1792-1822; Shelley, Mary Wollstonecraft / 1797-1851 / Drama; Shelley, Percy Bysshe / 1792-1822 / Drama; Women and literature / England / History / 19th century / Drama; Feature films; Biographical films; Romance films; Fiction films; Historical films; Film; DVD-Video